KKV-k innovációs aktivitása a Dél-alföldi Régióban - Vincze-Lendvai, Edina; Hódur, Sára (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
In the 20th century the role of the Universities has changed: the research has become important near the éducation. Nowadays there is a new, third function: the sale of the results on the market. We wanted to know what connections can be created between the University and the companies. Our aim to investigate the situation and attitudes of SMEs, in the Hungárián South Piain region.